2004
DOI: 10.1146/annurev.biochem.73.011303.073954
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of Intracellular Signaling Proteins: Regulation and Function

Abstract: Protein S-palmitoylation is the thioester linkage of long-chain fatty acids to cysteine residues in proteins. Addition of palmitate to proteins facilitates their membrane interactions and trafficking, and it modulates protein-protein interactions and enzyme activity. The reversibility of palmitoylation makes it an attractive mechanism for regulating protein activity, and this feature has generated intensive investigation of this modification. The regulation of palmitoylation occurs through the actions of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
497
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 543 publications
(510 citation statements)
references
References 174 publications
7
497
1
5
Order By: Relevance
“…Very recently, it has been shown that nSMase2 is S-palmitoylated in two Cys clusters; one cluster was located between the two hydrophobic segments, and the second one located in the middle of catalytic region of the protein [7]. Since S-palmitoylation is mostly restricted to the cytoplasmic side of the membranes [13], this posttranslational modification strongly supports the model presented in this study (proposed membrane topology and palmitoylation sites are shown in Fig. 6).…”
Section: Discussionsupporting
confidence: 88%
“…Very recently, it has been shown that nSMase2 is S-palmitoylated in two Cys clusters; one cluster was located between the two hydrophobic segments, and the second one located in the middle of catalytic region of the protein [7]. Since S-palmitoylation is mostly restricted to the cytoplasmic side of the membranes [13], this posttranslational modification strongly supports the model presented in this study (proposed membrane topology and palmitoylation sites are shown in Fig. 6).…”
Section: Discussionsupporting
confidence: 88%
“…Palmitoylation of proteins has several possible functions, depending on the protein under scrutiny. Much like protein prenylation in general, protein palmitoylation enables or contributes to membrane binding and possibly localization 52,53 . Additionally, palmitoylation may modulate protein-protein or protein-lipid interactions and enzyme activity.…”
Section: Palmitoylation Of Prenylated Proteinsmentioning
confidence: 99%
“…Increasing numbers of proteins have been shown to be covalently modified by the 16 carbon saturated fatty acid palmitate [1][2][3]. Attachment of palmitate to proteins occurs primarily via thio-ester linkage to cysteine (S-palmitoylation).…”
Section: Introductionmentioning
confidence: 99%
“…The saturated nature of the palmitoyl chain promotes insertion of the fatty acylated protein into liquid ordered membrane domains [10]. Palmitoylation also influences intracellular protein trafficking and targeting to specific subcellular membranes, protein-protein interactions and protein activity [3,11].…”
Section: Introductionmentioning
confidence: 99%